Relationship of physicochemical factors with fish biomass and production in Shadegan Wetland, Iran - SEYEDAHMADREZA HASHEMI; RASOUL GHORBANI; FARHAD KYMARAM; SEYED ABASS HOSSINI; GHOLAMREZA ESKANDARI; ALIAKBAR HEDAYATI (Biodiversitas Journal of Biological Diversity, 2016)
Hashemi S, Ghorbani R, Kymaram F, Hossini SA, Eskandari G, Hedayati A. 2016. Relationship of physicochemical factors with fish biomass and production in Shadegan Wetland, Iran. Biodiversitas 17: 515-522. The biomass of fishes was estimate in the Shadegan Wetland with Leslie model. Also the relationships between fish biomass and physic-chemical parameters of were studies. Sampling was carried out seasonally at five stations; include Atish, Khorosy, Mahshar, Rogbe, and Salmane from April 2013 to March 2014. During this study, 2795 specimens were measured and weighed. The highest fish biomass and lowest fish biomass were in springand winter seasons and Khorosy and Rogbe stations have highest and lowest fish biomass. The mean biomass of fish in four seasons Shadegan, 243Â±35 (kg/ha) and the amount of biomass in different seasons were not significantly different (P>0.05). Average values of water physicochemical parameters in different seasons were no significant (P>0.05), however average values of salinity stations were significant differences (P<0.05). Fish biomass regressions was estimated as Fish Biomass = 0.41 (temperature) 2.56. CCA ordination explained temperature, salinity, PH and DO, as the most important variables influencing the variation of fish composition in the Shadegan Wetland. Multi-layer artificial neural network showed four parameters (temperature, salinity, depth and DO) have the greatest impact on fish biomass.